2017
DOI: 10.1182/blood-2016-10-745059
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow microenvironment–derived signals induce Mcl-1 dependence in multiple myeloma

Abstract: Multiple myeloma is highly dependent on the bone marrow microenvironment until progressing to very advanced extramedullary stages of the disease such as plasma cell leukemia. Stromal cells in the bone marrow secrete a variety of cytokines that promote plasma cell survival by regulating antiapoptotic members of the Bcl-2 family including Mcl-1, Bcl-x, and Bcl-2. Although the antiapoptotic protein on which a cell depends is typically consistent among normal cells of a particular phenotype, Bcl-2 family dependenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
82
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 48 publications
5
82
0
Order By: Relevance
“…Our model was further validated by our studies of the S69E mutation. We previously reported that phosphorylation of Bim at S69 in multiple myeloma cells was associated with increased Bim binding to Mcl‐1 . When we applied our densitometry‐based analysis to RPCI‐WM1 cells overexpressing the S69E form of Bim, we observed a strong stabilization of Mcl‐1 despite relatively low Bim overexpression (Fig.…”
Section: Resultsmentioning
confidence: 66%
See 4 more Smart Citations
“…Our model was further validated by our studies of the S69E mutation. We previously reported that phosphorylation of Bim at S69 in multiple myeloma cells was associated with increased Bim binding to Mcl‐1 . When we applied our densitometry‐based analysis to RPCI‐WM1 cells overexpressing the S69E form of Bim, we observed a strong stabilization of Mcl‐1 despite relatively low Bim overexpression (Fig.…”
Section: Resultsmentioning
confidence: 66%
“…We've shown that Bim plays a role in stabilizing Mcl‐1 in myeloma cells, even in cells that were strongly dependent on Bcl‐2/x L for survival (Fig. C) . Mcl‐1 is overexpressed in many cancers including myeloma, frequently due to chromosome 1q amplification .…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations